CAN MONEY BUY CONVENIENCE: A STUDY ON INCOME AS A MOTIVATOR OF ONLINE SHOPPING? - Pallabi Mishra (Management & Marketing)
The fast and hectic life of professionals has created an essence of convenience and urgency in their activities and behavior. With the advent of technology and the swift internet era online activities are on a growing trend. This growing trend in online shopping has led to the consideration of this paper which aims to explore the role of individual income as a motivator of online shopping behavior. This study is descriptive in nature. It consists of primary survey of customers belonging to different individual income levels. The researcher has classified respondents on the basis of their individual income earned per annum into low, medium and high category. It investigates the influence of demographic factor income on shopping experiences of users of the major shopping websites of India. Data has been collected both from primary as well as secondary sources. The sampling technique used is convenience with a sample size of 755.The research results reveal that there is no significant effect of income on product categories purchased online. The effect of income on frequency of online shopping is not significant. There is no significant effect of income on payment mode in online shopping. Further there is no significant relationship between income and satisfaction in online shopping.The managers can benefit immensely from the results. Customers are offer driven in case of all items except necessary and emergency goods. The necessary items would sell even if there is no discount and offers on them. For other items offers and discounts influence the shopping behavior. The higher the offer the better the sale. Moreover to gain competitive advantage online marketers need to provide products and brands of higher value to customers. The cash on delivery facility should be applied to all product categories across the country so that every customer benefits from it. Care should be taken to manage reverse logistics as there should be a pick up facility from the delivered address if the product is not liked by the customer. Other services associated with the shopping process such as customer complaint handling and order processing should be made easier and smoother.This paper studies the gap in literature on motivator of individual income on online shopping trend. Extant literature has found studies on the relationship between household income and online shopping but not on individual income. Moreover the income has been categorized into low, medium and high levels of income as motivators for online buying behavior. It further draws on the research domino effects for implications for shopping website management and design, then suggests some ways to enhance performance for the website shopping industry.